Zoomorficzne aspekty obrazu Boga w Piśmie Świętym związane z bydłem domowym (Bos taurus taurus) - Wajda, Anna Maria (Verbum Vitae, 2017)
The present article examines the motif of cattle (Bos taurus taurus) as it was employed by biblical authors for the purpose of depicting God’s qualities and actions. The main aim of the study is to show the zoological and cultural background of the biblical symbols as it is rooted in the breeding and raising of domestic cattle. Namely, it is very probable that certain characteristics of cattle, such as their power, vitality and independence, were the stimulus for referring their image to God. The paper consists of the following parts: (1) a short report on the role of cattle in the beliefs and rituals of the ancient Near East, Greece and Rome; (2) an explanation as to how an ancient people’s knowledge of farm animals influenced their representing the power of God with the symbol of a bull; and (3) the presentation of selected issues concerning the biblical meaning of the horns of cattle.